Sensitivity of some species of pathogenic bacteria to the aquatic extract of local acacia Myrtus communis - Dhuha mohammed; Adeeba Shareef; Saad AL-Hafodhi (College of Education for Pure Sciences, 2008)
ABSTRACT The present investigation aimed to evaluate the effect of aqueous Extract Of Fruits Myrtus communis at different concentration (3.1, 6.2, 12.5, 25, 50, 100, 200, 400) mg/cm3 on the growth and viability of eight pathogenic bacteria the following bacteria were sensitive to the extract (Staphylococcus aureus, Escherichia coli, Salmonella typhi, Bacillus subtilis, Pseudomonas aeruginosa). while Klebsiella pneumonia, Proteus vulgaris and Serratia marcescens were resistant . The results showed that the effect of the extract was proportionally increased. With increasing the concentrations up to 12.5 mg/cm3. However the DIZ (mm) values for the bacteria (Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella typhi, Escherichia coli, Bacillus subtilis). Were (17.54, 14.75, 12.66, 12.08 and 9.29) mm respectively Also the values of minimum inhibitory concentration MIC (mg / cm3) for proceeding. Pathogenic species were (12.5, 25, 50, 50 and 100) mg/cm3 respectively.